2020
DOI: 10.1371/journal.pone.0242267
|View full text |Cite
|
Sign up to set email alerts
|

Employee burnout and positive dimensions of well-being: A latent workplace spirituality profile analysis

Abstract: In recent years, a new and promising construct has attracted the attention of organizational research: Workplace spirituality. To investigate the role of workplace spirituality in organizational contexts, two studies were carried out. Study 1 explored the mediation role of workplace spirituality in the relationship between positive supervisor behaviors and employee burnout. Results showed that workplace spirituality strongly contributes to reduce burnout and mediates the effect of supervisor integrity in reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 84 publications
2
32
0
Order By: Relevance
“…According to the motivational process of the JD-R, job resources may play a motivational role (either intrinsic or extrinsic), thus leading to high work engagement and better job performance [ 23 , 64 ]. Furthermore, a lack of job resources precludes that job demands are met and that work goals are reached, which may result in job burnout [ 65 67 ]. In addition, in line with the buffer hypothesis of the JD-R, job resources may buffer the association between job demands and negative outcomes including job burnout [ 21 , 68 70 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the motivational process of the JD-R, job resources may play a motivational role (either intrinsic or extrinsic), thus leading to high work engagement and better job performance [ 23 , 64 ]. Furthermore, a lack of job resources precludes that job demands are met and that work goals are reached, which may result in job burnout [ 65 67 ]. In addition, in line with the buffer hypothesis of the JD-R, job resources may buffer the association between job demands and negative outcomes including job burnout [ 21 , 68 70 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its ultimate goal is to improve the well-being, health, and performance of employees, both individually and as a group. Considering the data provided by the World Health Organization -WHO, which highlight anxiety and stress as an important risk factor for the well-being of employees and the company in general, it is essential that preventive, training, and intervention measures are adopted at the work process management level (Dal Corso et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Galea (2014) found that spirituality was related to lower burnout among nurses in difficult situations, even after adjusting for personality and well-being. In a study of 315 Italian employees (Dal Corso et al 2020), workplace spirituality had a negative direct effect on burnout and mediated the relationship between supervisor integrity on employee burnout. Hong (2012) noted the effect of perceived workplace spirituality on intention to leave in a sample of community mental health center professionals.…”
Section: Spirituality At Work As a Moderating Resourcementioning
confidence: 98%
“…Although the literature on the role of spirituality in organizations has proliferated in the past few decades (Dal Corso et al 2020), there is still a shortage of studies exploring spirituality at work as a potential buffer between job demands and negative job outcomes such as burnout and turnover intention. Therefore, within the framework of the JD-R and COR theories and based on the results of previous studies on the benefits of spirituality, we expand our mediational model by including spirituality at work as a potential moderator of the relationships between job demands, burnout, and turnover intention.…”
Section: Spirituality At Work As a Moderating Resourcementioning
confidence: 99%